2013
DOI: 10.1021/jp400372t
|View full text |Cite
|
Sign up to set email alerts
|

Electronically Excited States in Poly(p-phenylenevinylene): Vertical Excitations and Torsional Potentials from High-Level Ab Initio Calculations

Abstract: Ab initio second-order algebraic diagrammatic construction (ADC(2)) calculations using the resolution of the identity (RI) method have been performed on poly-(p-phenylenevinylene) (PPV) oligomers with chain lengths up to eight phenyl rings. Vertical excitation energies for the four lowest π–π* excitations and geometry relaxation effects for the lowest excited state (S1) are reported. Extrapolation to infinite chain length shows good agreement with analogous data derived from experiment. Analysis of the bond le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
97
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(108 citation statements)
references
References 53 publications
(117 reference statements)
7
97
4
Order By: Relevance
“…Comparing SVP and TZVP BS, they concluded that the flexibility of TZVP was needed for both RI-ADC(2) and RI-CC2 calculations [45]. An investigation of BS effects at the ADC(2) level was also performed on poly-(p-phenylenevinylene) oligomers, using SV, SV(P), TZVP and TZVPP for chains up to seven unit cells (the largest BS was applied up to the tetramer) [46]. It was concluded that going from SVP to TZVP induces a decrease in the excitation energies by ca.…”
Section: Literature Surveymentioning
confidence: 99%
“…Comparing SVP and TZVP BS, they concluded that the flexibility of TZVP was needed for both RI-ADC(2) and RI-CC2 calculations [45]. An investigation of BS effects at the ADC(2) level was also performed on poly-(p-phenylenevinylene) oligomers, using SV, SV(P), TZVP and TZVPP for chains up to seven unit cells (the largest BS was applied up to the tetramer) [46]. It was concluded that going from SVP to TZVP induces a decrease in the excitation energies by ca.…”
Section: Literature Surveymentioning
confidence: 99%
“…10 However, also the potential of this latter methodology has already been exploited by a number of researchers studying organic electronics and photobiology. [16][17][18][19][20] A unified formalism is present through the use of one-particle density matrices (1DM) and transition density matrices, a common ground, which allows for a clear comparison between the different methods and suggests extensions leading to a wide variety of routines for population analysis, as well as, orbital and density plotting, which are provided in this implementation. To our knowledge, a similarly comprehensive analysis toolbox has not been made available so far, let alone in a correlated ab initio framework.…”
Section: Introductionmentioning
confidence: 99%
“…Molecules with extended π -systems occupy an intermediate position between these two extremes. 17,23 While the "quantum chemistry" picture is certainly able to provide a large amount of insight for these systems, there are some pieces of information which are invariably lost, when the elec- tron and hole are viewed independently. Electron-hole correlations are the very property distinguishing excitons from free charge carriers, and their extent is the key difference between strongly bound Frenkel excitons and weakly bound Wannier excitons.…”
Section: Introductionmentioning
confidence: 99%
“…We employed the theoretical method based on the single-electron transition density matrix [95][96] for such analysis. Because this method was explicitly discussed in previous studies, 36,[95][96][97][98][99] we only outline the main idea here, and all the details are given in Figure S1, Supporting Information. The one-electron transition density matrix in Löwdin's 95 atomic-orbital basis is obtained by: 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 15 orthogonalization of Löwdin's atomic orbitals, the transition contribution between different atoms simply becomes…”
Section: Transition Density Analysismentioning
confidence: 99%
“…To describe such collective alternation, the socalled bond length alternation (BLA, in Scheme 2) coordinates are employed. [35][36][37] For the sixmember conjugated ring, the BLA parameter d R is defined as …”
Section: Introductionmentioning
confidence: 99%